Clinicians perspectives on nutritional supplementation and polycystic ovary syndrome management in women in Indian settings - S., Manjula; M., Krishna Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Although there were several clinical studies available, there was a dearth of studies among clinicians in actual practice. So, this study seeks to gather expert perspectives on protein supplementation and the management of polycystic ovary syndrome (PCOS) among women, with a special focus on the myo-inositol and D-chiro-inositol combination in Indian settings. Methods: This cross-sectional study was conducted using a 24-question multi-response questionnaire directed at clinicians. The survey explored practices and opinions on protein supplementation, including frequency, target populations, nutritional status, and timing. It also investigated PCOS prevalence, symptoms, types, treatment recommendations, and dietary adjustments. The perceived effectiveness of myo-inositol and D-chiro-inositol combinations, particularly in conjunction with hormonal therapy and in vitro fertilization (IVF), was assessed. Data were analyzed using descriptive statistics. Results: Most clinicians (96.59%) identified pregnant or lactating women as the primary group requiring protein supplementation, with 72.73% recommending 26 grams per day. Nearly 95% reported PCOS was commonly diagnosed in women aged 18 to 44 years, and 72% noted that insulin resistance PCOS was more prevalent. Infertility was cited as the main impact of unmanaged PCOS by 67% of respondents. Approximately 43% of clinicians found the myo-inositol and D-chiro-inositol (40:1 ratio) combination to improve PCOS treatment significantly. Additionally, 40% of the experts reported that the supplementation enhances ovarian function, 31% noted improved menstrual cycle regularization, and 77% reported benefits in ovulation, folliculogenesis, and egg quality when combined with IVF. Conclusions: This study highlighted the importance of protein supplementation for pregnant and lactating women and supports the myo-inositol and D-chiro-inositol combination as a beneficial treatment for PCOS.